Physical properties and biocompatibility of an injectable calcium-silicate-based root canal sealer: in vitro and in vivo study. Issue 1 (December 2015) - Lim, Eun-Su; Park, Young-Bae; Kwon, Young-Sun; Shon, Won-Jun; Lee, Kwang-Won; Min, Kyung-San
Abstract Background The aim of this study was to investigate the physical properties and biological effects of an experimentally developed injectable premixed calcium-silicate root canal sealer (Endoseal) in comparison with mineral trioxide aggregate (MTA) and a resin-based sealer (AHplus). Methods The pH, solubility, dimensional change, flow, and radiopacity of the materials were evaluated. Biocompatibility was evaluated on the basis of cell morphology and a viability test using MC3T3-E1 cells. For evaluate inflammatory reaction, the tested sealers were implanted into dorsal subcutaneous connective tissue of Sprague Dawley rats. After 7 days, the implants with the surrounding tissue were retrieved, and histological evaluation was performed. Results Endoseal showed high alkalinity similar to that of MTA. The solubility of the tested materials was similar. The dimensional change and flow of Endoseal was significantly higher than that of other materials (P  < 0.05). The radiopacity of Endoseal was lower than that of AHplus (P  < 0.05). The biocompatibility was similar to those of MTA. Inflammatory reaction of Endoseal was similar with that of MTA, but lower than that of AHplus (P  < 0.05). Conclusions The present study indicates that Endoseal has favorable physical properties and biocompatibility. Therefore, we suggest that Endoseal has the potential to be used as a predictable root canal sealer.